EFL Students' Challenges in Delivering a Presentation by Peer Assessment - Aini, Tika; Febriani, R. Bunga; Iskhak, Ishak (Universitas Galuh, 2025)
This research discusses students' challenges in delivering English presentations using peer assessment. The purpose of this research is to determine the challenges faced by students in delivering English presentations using peer assessment and to find out whether or not students can overcome the obstacles in delivering English presentations using peer assessment. This research used a qualitative case study method involving 5 class VIII students in learning to deliver English presentations using peer assessment. Semi-structured interviews and observations were used in this research and were analyzed by using thematic analysis. The results show that students responded positively to the use of peer assessment in delivering English presentations. Most students feel insecure because they lack confidence when they must deliver English presentations and be assessed by their classmates. Formative peer assessment is also an effective medium for students to question their friends' performance. Researchers suggest that future research can focus on using peer assessment methods to help students reducing the challenges students face in delivering English presentations.